Ants, Rationality, and Recruitment - Kirman, A. (Quarterly Journal of Economics, 1993)
This paper offers an explanation of behavior that puzzled entomologists and economists. Ants, faced with two identical food sources, were observed to concen-trate more on one of these, but after a period they would turn their attention to the other. The same phenomenon has been observed in humans choosing between restaurants. After discussing the nature of foraging and recruitment behavior in ants, a simple model of stochastic recruitment is suggested. This explains the "herding " and "epidemics " described in the literature on financial markets as corresponding to the equilibrium distribution of a stochastic process rather than to switching between multiple equilibria. In a series of experiments entomologists [Deneubourg et al., 1987a; Pasteels et al., 1987a] observed that ants in an apparently symmetric situation behaved, collectively, in an asymmetric way. When faced with two identical food sources, the ants exploited one more intensively than the other. Furthermore, from time to time they switched their attention to the source that they had previ-